Emergency obstetric and newborn care: A priority measure to achieve rapid decline in maternal and newborn mortality in sub-Saharan Africa - Friday Okonofua; Lorretta Favour Chizomam Ntoimo (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
For more than three decades, sub-Saharan Africa has invested heavily in the five WHO pillars of safe motherhood.1,2 Governments, development partners, professional associations and civil society organizations have promoted family planning, strengthened antenatal care, expanded skilled birth attendance, improved postnatal care, and, where permitted by law, advocated for safe abortion services. These interventions have undoubtedly contributed to improved maternal and newborn health and have saved countless lives. Yet the region continues to account for approximately 70% of global maternal deaths.3 The persistence of this unacceptable burden raises an important question: why have these investments not translated into the dramatic reductions in maternal mortality that many had anticipated? The answer possibly lies in a fundamental but often overlooked reality. Pregnancy is inherently unpredictable. Even among women who receive excellent antenatal care, attend all scheduled clinic visits, and are cared for by skilled birth attendants, life-threatening obstetric complications can develop suddenly and without warning. Haemorrhage, eclampsia, obstructed labour, sepsis, uterine rupture, complications of abortion, and severe neonatal asphyxia frequently occur in women previously considered to have low-risk pregnancies. When these emergencies arise, preventive interventions have already reached their limits. At that critical moment, emergency obstetric and newborn care (EmONC) becomes the only intervention capable of preventing death.